UAV payload virtualization based on the unified driving and capability abstraction - LI Xiaojuan; ZHOU Xingshe; ZHANG Yu; YAO Yuan; YANG Gang (Xibei Gongye Daxue Xuebao, 2024)
As UAV and swarms applications continue to deepen and become increasingly widespread, UAV payloads have characteristics such as diverse types, heterogeneous forms, and complex interfaces. At the same time, it is required that the system can quickly access and efficiently manage payloads. In order to decouple the close relationship between the payloads and the system platforms, and expand the compatibility with heterogeneous payloads, a novel payload device virtualization method is proposed. Firstly, a layered driver model is proposed to decouple the device hardware and device driver, standardize the payload access process, and the driver model is implemented by using the software and hardware. Secondly, a payload abstraction based on "capability" is proposed to decouple load application and device. Finally, specific examples for the verification of the virtualization method are implemented. The present UAV payload virtualization method can not only achieve software and hardware decoupling, but also enhance the compatibility and scalability of system, improving the efficiency of unified payload management.